Magnetic characteristics and fault tectonics of the earth's crust of the Shebelina group of gas fields as a component of the complex search criteria of hydrocarbons - M. I. Orlyuk; I. K. Pashkevich (Геофизический журнал, 2011)
It has been shown that gas deposits and gas-bearing structures of the Shebelynka area are controlled by the regional and local sources of magnetic field (ΔТ)a location as well as the fracture-blocky tec-tonics. This is the fundamental conclusion that is justified by a set of theoretical and experimental elaborations and analysis of anomalous magnetic field, regional magnetic model, theoretical mod-els of oil-gas-bearing structures, the faults systems and oil and gas-bearing capacity of the Earth’s crust. On the base of latest data on oil and gas-bearing collectors in the crystalline basement of the northern slope of depression and on the results of the magnetic modeling it was suggested that the confinement of deposits to the area of deep magnetic formations and to the faults of different types regurded as the ways of hydrocarbons migration may be the evidance of their inorganic origin. Confinement of deposits to local magnetic anomalies with sources in sedimentary rocks may be considered as a criterion for the hydrocarbons organic origin. A possibility of a «combined» gen-esis of hydrocarbons when deposits of organic origin are “supplied” by deep fluids over zones of deep-seated faults as oil-gas-transporting channels was discussed. The unique Shebelynka deposit apparently belongs to such a kind of deposits.